STUDENTS’ PERCEPTION OF THE ARTICLE “RUKHANI ZHANGYRU” BY THE PRESIDENT OF KAZAKHSTAN N. NAZARBAYEV - Danilova, V.V.; Bermuhametovа, A.A.; Asanova, A.B.; Ukanova, A. (PUBLISHINGS of Kostanay State Pedagogical University, 2018)
The article is written with the students of the Faculty of Philology. In March, a round table was held at the headline of the "Rukhani Zhangyru". The students were given an active part in the discussion of the article, which represents the development of the program in the Republic of Kazakhstan. During two months the students have been analyzing periodicals, watching television broadcasters, evaluating the situation in the Republic of Kazakhstan through the support of the Internet resources. The results of the analysis and observation are presented in the article.
Keywords: microteaching; group work; discussion; analysis; development